PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN PADA LEMBAGA KESEJAHTERAAN SOSIAL ANAK PUTRI (LKSAP) ‘AISIYAH DAU - Chalimatuz Sa'diyah; Kenny Roz (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2021)
Abstract. The dedication to Catering and Retail of the Children's Welfare Institution for Women (LKSAP) ‘Aisiyah Dau aims to increase knowledge about financial records, especially for children. The problem faced by partners is that they are less able to keep financial records up to making standard financial reports. Human resources at Catering and Retail of the Children's Welfare Institution for Women (LKSAP) isi Aisiyah Dau has education ranging from elementary school graduates to tertiary institutions, this causes difficulties in making the recording of cash, inventories and standardized accounts. The recording of standardized cash, inventories and receivables is indispensable for decision making for business managers in Catering and Retail LKSAP ‘Aisiyah Dau which they pioneered. The method of implementing the services carried out is by providing guidance, assistance, business development management training, administration training to recording cash, inventories and receivables. The output in this community service is that partners can actually make a record of cash, inventories and receivables independently, and can develop their business in terms of making income statements. This is necessary for the interests of partners in developing their business, so knowledge is needed, both in the field of recording in particular and business in general. The results of this community service activity are financial records in the form of bookkeeping regarding the recording of cash, receivables and inventories. The recording can help LKSAP ‘Aisiyah Dau in monitoring the financial of Catering and Retail owned so that it can be used for decision making.     Abstrak. Pelaksanaan pengabdian pada Catering dan Retail Lembaga Kesejahteraan Sosial Anak Putri (LKSAP) ‘Aisiyah Dau ini bertujuan untuk meningkatkan pengetahuan akan pencatatan keuangan khususnya pada anak-anak. Masalah yang dihadapi mitra adalah kurang mampu dalam membuat pencatatan keuangan sampai membuat laporan keuangan yang standar. Sumberdaya manusia pada Catering dan Retail Lembaga Kesejahteraan Sosial Anak Putri (LKSAP) ‘Aisiyah Dau memiliki pendidikan mulai lulusan SD sampai dengan perguruan tinggi, hal ini mengakibatkan kesulitan dalam pembuatan pencatatan kas, persediaan dan piutang terstandart. Pencatatan kas, persediaan dan piutang terstandart sangat diperlukan untuk pengambilan keputusan bagi pengelola usaha pada Catering dan Retail LKSAP ‘Aisiyah Dau yang mereka rintis. Metode pelaksanaan pengabdian yang dilakukan adalah dengan cara mengadakan pembinaan, pendampingan, pelatihan manajemen pengembangan usaha, pelatihan administrasi sampai dengan pencatatan kas, persediaan dan piutang. Luaran pada pengabdian masyarakat ini adalah mitra benar-benar dapat membuat pencatatan kas, persediaan dan piutang secara mandiri, dan bisa mengembangkan usahanya dalam hal pembuatan laporan laba rugi. Hal ini diperlukan untuk kepentingan mitra dalam mengembangkan usahanya, sehingga diperlukan pengetahuan, baik dibidang pencatatan khususnya maupun bisnis pada umumnya. Hasil dari kegiatan pengabdian ini adalah pencatatan keuangan dalam bentuk pembukuan mengenai pencatatan kas, persediaan dan piutang. Pencatatan tersebut dapat membantu LKSAP ‘Aisiyah Dau dalam memonitor keuangan Catering dan Retail yang dimiliki sehingga dapat digunakan untuk pengambilan keputusan.